Is chemotherapy always necessary for patients with nonmetastatic gestational trophoblastic neoplasia with histopathological diagnosis of choriocarcinoma? - Braga, Antonio; Campos, Vanessa; Rezende Filho, Jorge; Lin, Lawrence H.; Sun, Sue Yazaki; Souza, Christiani Bisinoto de; Alves Ferreira da Silva, Rita de Cassia; Soares Leal, Elaine Azevedo; Silveira, Eduardo; Maesta, Izildinha [UNESP]; Madi, Jose Mauro; Uberti, Elza H.; et al. (Elsevier B.V., 2018)
Objective. To evaluate expectant management versus immediate chemotherapy following pathological diagnosis of gestational choriocarcinoma (GCC) in patients with nonmetastatic disease. Methods. Multicenter retrospective cohort that included patients with histological diagnosis of GCC with nonmetastatic disease followed at one of thirteen Brazilian referral centers for gestational trophoblastic disease from January 2000 to December 2016. Results. Among 3191 patients with gestational trophoblastic neoplasia, 199 patients with nonmetastatic GCC were identified. Chemotherapy was initiated immediately in 152 (76.4%) patients per FIGO 2000 guideline, while 47 (23.6%) were managed expectantly. Both groups presented with similar characteristics and outcomes. All patients (n = 12) who had normal human chorionic gonadotropin (hCG) in the first 2-3 weeks of expectant management achieved complete sustained remission with no chemotherapy. Only 44.7% (21 patients) of patients who were expectantly managed needed to receive chemotherapy due to plateauing or rising hCG level in the first 2-3 weeks of follow up. The outcome of patients receiving chemotherapy after initial expectant management was similar to those who received chemotherapy immediately after the diagnosis in terms of need for multi-agent chemotherapy or number of cycles of chemotherapy. There was no case of relapse or death in either group. Logistic regression analysis showed that age >= 40 years and hCG >= 92,428 IU/L at GCC diagnosis were risk factors for needing chemotherapy after initial expectant management of nonmetastatic GCC. Conclusion. In order to avoid exposing patients unnecessarily to chemotherapy, close surveillance of women with pathological diagnosis of nonmetastatic GCC seems to be a safe practice, particularly for those who have a normal hCG at the time of diagnosis. If confirmed by other studies, the FIGO guidelines may need to be revised. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Gestational trophoblastic neoplasia; Choriocarcinoma; Human chorionic gonadotropin; Chemotherapy